Effect of the Composition of the Electrodes on the Efficiency of Thermal Cell - M. Sarhan, Waleed; N. Alkhateeb, Ahmed; H. Hussein, Falah (Asian Journal of Chemistry, 2010)
An efficient high temperature molten salt thermal cell has been constructed, which was composed of Ca or Mg as the anode. The cathode was produced by blending the three components viz., CaCrO4, K2CrO4 or K2Cr2O7 as the depolarizer (D), LiCl-KCl eutectic mixture as the electrolyte (E) and SiO2 as the binder (B). The influence of the cathode components (DEB) upon the efficiency of the thermal cell, where the anode was Ca, was investigated. It was found that the weight percentage of eutectic mixture (E): 55.2% KCl and 44.8% LiCl, gave the lowest eutectic point, namely, 355ºC. In addition, the weight percentages of the depolarizer (D); CaCrO4 and the binder, SiO2 of 83% and 17%, respectively, generated the maximum produced voltage of 0.8 V at 460–465C. However, mixtures of 75% K2Cr2O7 and 25% SiO2, 30% K2CrO4 and 70% SiO2 gave voltages of 0.41 and 0.48 volts. Using Mg anode with the same eutectic mixture, a mixture of 90% CaCrO4 and 10% SiO2, 78% K2Cr2O7 and 22% SiO2 gave voltages of 0.42 and 0.44 V, respectively, indicating that Ca is more efficient than Mg. Thermal analysis study for the electrolyte in the absence of the depolarizer, CaCrO4, using the differential scanning calorimeter (DSC) showed that the beginning of LiCl-KCl mixture eutectic point was 343ºC, where the enthalpy was 23.3 J g–1. However, using CaCrO4 as a depolarizer gave a eutectic point of 380ºC, where the enthalpy was 88 J g–1, which is much greater than that in the absence of the depolarizer, and hence a higher voltage, 80 V, was generated. Using K2Cr2O7 as a depolarizer gave a eutectic point of 299ºC and enthalpy of 40 J g–1, which is half that found with CaCrO4. In addition, usage of K2CrO4 revealed a eutectic point of 359ºC and a lesser enthalpy, that is, 20.8 J g–1, and consequently a lower voltage was produced.